1993
DOI: 10.1302/0301-620x.75b6.8245082
|View full text |Cite
|
Sign up to set email alerts
|

Glove perforation during hip arthroplasty. A randomised prospective study of a new taperpoint needle

Abstract: Exposure to blood is a hazard for all surgeons.We assessed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…There has been shown to be a reduced rate of glove puncture and needlestick injury by the use of blunt tipped needles, both in obstetrics and other surgical specialities (Corlett, 1993;Wright, 1993;Dauleh, 1994;Miller, 1994;Thomas, 1995;Ablett, 1998). We have demonstrated a trend towards a reduction in glove puncture rates from the use of blunt-tipped needles in perineal repair (Ablett et al, 1998).…”
Section: Blunt-tipped Needlesmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been shown to be a reduced rate of glove puncture and needlestick injury by the use of blunt tipped needles, both in obstetrics and other surgical specialities (Corlett, 1993;Wright, 1993;Dauleh, 1994;Miller, 1994;Thomas, 1995;Ablett, 1998). We have demonstrated a trend towards a reduction in glove puncture rates from the use of blunt-tipped needles in perineal repair (Ablett et al, 1998).…”
Section: Blunt-tipped Needlesmentioning
confidence: 99%
“…However, some operators may need to use the needles a few times in order to familiarise themselves with this technique (Lewis et al, 1995). Their use in comparison to sharp needles has been studied in many surgical and orthopaedi c procedures and the results have shown conclusively that they greatly reduce the number of glove and skin punctures occurring during operating (Wright et al, 1993;Dauleh, 1994;Miller and Sabharwal, 1994). A recent study from St Mary's Hospital, London, has shown a decrease in glove puncture rate at lower segment caesarean section from 51% to 34% (Thomas et al, 1995).…”
Section: Blunt-tipped Needlesmentioning
confidence: 99%
“…During surgery, using sterile gloves acts as a protective barrier against pathogens present in blood and skin, such as human immunodeficiency virus and hepatitis B and C and several common bacteria [2-9]. Because of its importance and because of the risk of perforation during surgery, the use of two gloves has generally been adopted by most surgical teams in numerous situations as a way to reduce the risk of perforation, although this measure was not included in WHO recommendations on safety in surgery, since there are no sufficient studies to prove their efficacy [3,4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The use of latex gloves is the current standard of protection during surgery, providing enough security to the patient and surgical team, as they remain intact throughout the procedure [2-9]. However, several conditions have been linked to increased risk of glove perforation during surgery, such as frequent handling of sharp instruments and prolonged procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Double gloving, 1,2 the wearing of outer 'orthopaedic' gloves or cloth gloves between two pairs of gloves 3 and the use of a taperpoint needle 4 have reduced the incidence of needlestick injuries. The Regent Biogel Reveal double-gloving system (Regent Hospital Products, Broxbourne, UK) was developed to increase the surgeon's awareness of glove perforation.…”
mentioning
confidence: 99%